SISTEM INFORMASI PERENCANAAN PENJUALAN DAN DISTRIBUSI BARANG PADA PT GANDUM MAS KENCANA TANGERANG - Jose Josua Sinaga (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2021)
This study aims to make it easier for salesmen, branch managers and data analyzers to make requests to supply goods at distribution centers by creating a sales and distribution planning website at PT Gandum Mas Kencana Tangerang. Making this application using PHP (Hypertext Prepocessor) as a programming language and MySQL as a database. The required data is obtained at PT Gandum Mas Kencana Tanggerang. Data collection was carried out by observation and interviews to the research location. The method used in making this application is the waterfall method. The results of this study indicate that a website is needed to assist salesmen, branch managers and data analysis in planning sales and distribution of goods. And also make it easier for PT Gandum Mas Kencana Tangerang to perform data processing and data storage.